HUBUNGAN KONDISI GEOLOGI TERHADAP ALTERASI HIDROTERMAL DAN MINERALISASI PADA ENDAPAN EPITERMAL DAERAH BUNIKASIH, KECAMATAN TALEGONG, KABUPATEN GARUT, PROVINSI JAWA BARAT - Saumi Rahmawati; Hadi Nugroho; Dian Agus Widiarso; Okky Verdiansyah (Geological Engineering E-Journal, 2013)
Hydrothermal alteration is a changed in the mineral composition of the rock as a result of interaction of hydrothermal fluids with the wall rock involving various geological environments like fault zones and volcanic eruptions zones. Hydrothermal alteration has a very close relationship with the mineralization. Mineralization is a process of inclusion of valuable rare minerals in rocks that form ore deposits. The purpose of this study is to determine the geological conditions of the mapping area and knowing the type of alteration and the relationship between alteration with the developing of ore mineralization. Research methods include field observations survey and continued by analysis methods, conducted in Bunikasih and surrounding areas, Talegong District, Garut regency, West Java. Methods of analysis undertaken include petrology, petrography, Terraspec, and structure analysis. Geological conditions of the study area consists geomorphological unit of structural steep hills and undulating hills of volcanic units (Van Zuidam, 1983). The research area is composed by rocks from old to young volcanic breccia, Andesite Lava, and tuff. Geological structures that are left slip fault of North Cibaliung, right slip thrust fault of South Cibaliung, right slip normal fault of Citutugan-Cibaliung Beet. There are prophylitic alteration (smectite, chlorite, ±illite), argillic (kaolinite, illite, smectite), advanced argillic (kaolinite, illite, alunite, silica), and silicification (vein zone). In the study area there are two types of epithermal, low sulfidation epithermal zone on Bunikasih mineralized was found that quartz manganese vein, chalcedonic vein, crustiform-colloform banded vein, and disseminated pyrite. there are 5 main vein lines with 40-100cm of thickness with a northwest-southeast direction formed on andesite and tuff, due to the style of the extensions that form the structure openings fault trending Northwest-Southeast. At high sulphidation epithermal indication zone in Datarkorot is dominated by advanced argillic alteration. Mineralization occurred is in the disseminated pyrite form and the concentrated hematite oxide mineral, goethite, and jarosite is a condition of changing sulfide mineral acids. Mineralization is controlled by lithology, by tuff unit which is interpreted lithocap of a diaterme breccia generated by a dacite porphyry intrusion.